2013
DOI: 10.1002/jgrd.50156
|View full text |Cite
|
Sign up to set email alerts
|

A climatology of frozen‐in anticyclones in the spring arctic stratosphere over the period 1960–2011

Abstract: During springtime, following the stratospheric final warming, intrusions from low latitudes can become trapped at polar latitudes in long‐lived anticyclones. Such “frozen‐in” anticyclones (FrIACs) have occasionally been observed to persist as late as August, advected by summer easterlies.In this study, the high‐resolution advection contour model MIMOSA is used to advect a pseudo‐potential vorticity tracer. The model is driven by ERA‐40 and the ERA‐Interim reanalyses over the period 1960–2011. We first identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…NOGAPS-ALPHA is the high-altitude extension of the then operational Navy's weather forecast system up to about 90-92 km (Eckermann et al, 2009 . Then, in early April (Day 95) of that year, the largest FrIAC of the 36-year MERRA dataset was recorded (Allen et al, 2011;Thieblemont et al, 2013), causing a significant jump in upper stratospheric CH 4 . After the spring, there is a second period of decreasing CH 4 in the summer (most noticeable after day 200).…”
Section: The Whole Atmosphere Community Climate Model (Waccm)mentioning
confidence: 99%
“…NOGAPS-ALPHA is the high-altitude extension of the then operational Navy's weather forecast system up to about 90-92 km (Eckermann et al, 2009 . Then, in early April (Day 95) of that year, the largest FrIAC of the 36-year MERRA dataset was recorded (Allen et al, 2011;Thieblemont et al, 2013), causing a significant jump in upper stratospheric CH 4 . After the spring, there is a second period of decreasing CH 4 in the summer (most noticeable after day 200).…”
Section: The Whole Atmosphere Community Climate Model (Waccm)mentioning
confidence: 99%
“…Waugh and Rong () also showed strong differences in the polar vortex mixing processes with midlatitude air in association with the SFW timing. More recently, Thiéblemont et al (, ) revealed that early SFWs are more likely to feature “Frozen‐In” anticyclone occurrences in spring and summer (Manney, Livesey, et al, ), which lead to anomalously high nitrous oxide and methane concentrations in the polar stratosphere. However, not only does the variability of SFW timing alter the stratospheric composition and circulation, but it is also associated with tropospheric anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two climatologies of FrIACs starting in 1979 [ Allen et al ., ] and 1960 [ Thiéblemont et al ., ] and based on MERRA (Modern Era‐Retrospective Analysis for Research and Applications) and ECMWF ERA‐40/ERA‐Interim (European Centre for Medium‐Range Weather Forecasts Re‐Analysis) reanalyses, respectively, were performed. Despite the use of different reanalyses, transport models, and FrIAC detection algorithms, both studies revealed largely consistent results with common FrIACs identified in the springs of 1982, 1994, 1997, 2002, 2003, 2005, and 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Thiéblemont et al . [] identified FrIACs by requiring low‐latitude air masses in the polar region (northward of 60°N) to be colocated with an anticyclonic eddy until, at least, the beginning of the shearing phase (see Thiéblemont et al . [] for a detailed discussion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation